Дослідник Успенського собору Києво-Печерської лаври: до 120-річчя від дня народження М. В. Холостенка - Абашина, Н.С. (Археологія, 2022)
У статті розглянуто життєвий шлях і творчий
доробок видатного українського архітектора, дослідника й реставратора пам’яток архітектури, педагога Миколи В’ячеславовича Холостенка
(1902—1978). Значне місце в його діяльності посідають дослідження Успенського собору Києво-Печерської лаври, за результатами яких він простежив архітектурну історію пам’ятки та відтворив
первинний вигляд собору й виконав реконструкцію
церкви св. Іоанна Предтечі. December 7, 2022 marks the 120th anniversary of the birth of the outstanding Ukrainian architect, historian of national architecture,
researcher and restorer of architectural monuments, teacher Mykola Viacheslavovych Kholostenko (1902—1978). After
graduating from the Kyiv Institute of Architecture in 1929, he taught at the Kyiv Institute of Civil Engineering and Art Institute,
managed the design workshop of the Kyiv City Council (1938—1941), worked at the Kyivproject Institute (1953—1958,
1961—1977), held the position of chief architect of the Republican Special Research and Restoration Production Workshops
State Construction Committee of the USSR (1959—1961).
In addition to the development of projects of residential and public buildings in Kyiv, M. V. Kholostenko had done a lot of
work on the study, protection and restoration of architectural monuments of the 10th—18th centuries of Kyiv, Chernihiv, Putyvl,
Novhorod-Siverskyi.
M. V. Kholostenko’s contribution to the study of the Cathedral of the Dormition of the Kyiv-Pechersk Lavra is significant.
Many years of research (1952—1954, 1962—1963, 1969—1972) allowed him to trace the architectural and construction history
of the entire ecclesiastical complex. M. V. Kholostenko found out the construction and technical features of the ancient part of
the cathedral — the technology of making plinths, the method of masonry of the main walls, arches, vaults. He was the first who
systematized and classified the bricks of the Cathedral of the Dormition of the 11th—17th centuries.
During the research, new, previously unknown elements of the architecture of the ancient part of the cathedral were discovered,
hidden behind later extensions. M. V. Kholostenko developed a scheme of dimensions and proportions of the cathedral of the 11th
century and corrected the general plan of the temple and its individual parts.
The results of architectural and archaeological research of the remains of the cathedral and the analysis of iconographic
sources provided sufficient grounds for the scientific reproduction of the entire cathedral complex. M. V. Kholostenko was one
of the first to recreate the original appearance of the Cathedral of the Dormition and reconstructed the Church of St. John the
Baptist. The results of his research became the basis for the development of the project for the restoration of the Cathedral of the
Dormition of the Kyiv-Pechersk Lavra, implemented in 1998—2000.